1998
DOI: 10.4269/ajtmh.1998.59.438
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of hantavirus infection in Indian communities of the Paraguayan and Argentinean Gran Chaco.

Abstract: Serologic evidence of past infection with a Sin Nombre-like hantavirus(es) was demonstrated in 78 (40.4%) of 193 Indians living in western Paraguay and in 38 (17.1%) of 222 Indians inhabiting the Salta province of northern Argentina. In both populations seroprevalence increased with age, with the most striking increase occurring at 18 years of age in the Paraguayan population and at 35 years of age in the Salta population. The peak prevalences in both populations (66.6% and 44.0%, respectively) were seen in In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
43
2
6

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 25 publications
4
43
2
6
Order By: Relevance
“…The low seroprevalence of IgG antibodies in the Novo Progresso, Trairão and Guarantã do Norte (ranging from 2.16-4.75%) is in accordance with the data from Brazilian HPS cases (Holmes et al 2000, MS/SVS 2009, while in Marcelândia, the seroprevalence was similar to that observed in the Amazon area of MA (Mendes et al 2001(Mendes et al , 2010, as well as in Chile (Castillo et al 2002) and Paraguay (Ferrer et al 1998).…”
Section: Discussionsupporting
confidence: 75%
“…The low seroprevalence of IgG antibodies in the Novo Progresso, Trairão and Guarantã do Norte (ranging from 2.16-4.75%) is in accordance with the data from Brazilian HPS cases (Holmes et al 2000, MS/SVS 2009, while in Marcelândia, the seroprevalence was similar to that observed in the Amazon area of MA (Mendes et al 2001(Mendes et al , 2010, as well as in Chile (Castillo et al 2002) and Paraguay (Ferrer et al 1998).…”
Section: Discussionsupporting
confidence: 75%
“…8 Similar seroprevalence rates in Paraguay 9 and Brazil 10-12 may also be consistent with frequent mild disease that does not require hospitalization but may pose a significant economic burden. The identification of all HV infections will improve environmental risk assessments, public health intervention planning, and HV vaccine field evaluations.…”
Section: Discussionmentioning
confidence: 78%
“…4,6 A high prevalence of HV antibodies in serum, ranging from 12% to 45%, was noted in neighborhoods of HPS patients 3 and community-wide surveys 7,8 among individuals who had no history of hospitalization for respiratory insufficiency. A comparably high seroprevalence found in northern Argentina and Paraguay 9 and in Brazil [10][11][12] contrasts with low seroprevalence in Andes virus-endemic regions. 13,14 In four Panama communities, repeated seroprevalence surveys found that history-negative infections outnumbered hospitalized HPS in the same region by a ratio of 14:1.…”
Section: Introductionmentioning
confidence: 91%
“…n the Americas, hantavirus species that occur at low frequency are associated with the severe disease hantavirus pulmonary syndrome (HPS) (1,2), and species that occur at higher frequency are associated with milder disease (3)(4)(5). In Panama, HPS is caused by the Choclo virus, for which a common rodent, the fulvous pygmy rice rat (6), is host.…”
mentioning
confidence: 99%